CCNA2 and CCND2 are differentially involved in β-cell proliferation in perinatal Japanese autopsied subjects - Osonoi, Sho; Sasaki, Takanori; Wang, Zhenchao; Tarusawa, Takefusa; Osonoi, Kasumi; Ishiyama, Emi; Kushibiki, Hanae; Ryuzaki, Masaki; Tu, Yi; Fujita, Yukihiro; Terui, Kiminori; Yagihashi, Soroku; et al. (The journal of clinical endocrinology and metabolism, 2025)
β-cell proliferation is restricted to the perinatal period. Although cyclins trigger cell proliferation, their contribution to cell proliferation during the human perinatal period is not well understood. Furthermore, histological changes in the development of islet cells in Japanese are not well understood. Determine pancreatic islet formation with cyclin involvement from the perinatal period to adolescence in Japanese autopsy samples. Forty-seven formalin-fixed paraffin-embedded pancreas sections from fetuses to adolescents were morphometrically evaluated. The expression of nuclear cyclins A2 and D2 was evaluated by immunohistochemistry. CCND2 and CCND2-antisense 1 lincRNA were evaluated by in situ hybridization. α- and β-cell proportions increased with development. The β-/α-cell ratio was almost constant during development. β-cell proliferation, as revealed by labeling with antibodies against Ki-67, was most abundant around birth and then rapidly decreased. The expression of nuclear cyclins A2 and D2 was highest around birth, and there was a stronger positive correlation between the Ki-67 index and cyclin A2 than D2. The expression of CCND2- antisense 1 lincRNA in pancreatic islets decreased rapidly after birth and correlated more significantly with cyclin D2 expression than with CCND2 mRNA expression. Our results provide the first morphological changes during the islet cell development in Japanese autopsy samples, ranging from fetuses to adolescents and that CCNA2, assisted by CCND2, may play a central role in β-cell proliferation. Furthermore, CCND2-antisense 1 positively regulates cyclin D2 expression in pancreatic islets of during development. These results could be applied to future β-cell proliferation therapies.